Social-Emotional Learning for Teachers - Madora Soutter (University of Windsor, 2023)
Social and emotional learning (SEL) is a crucial part of student wellness and academic achievement, but teachers' own SEL is often overlooked. This qualitative study examines educators' perceptions of their own university-level teacher preparation programs to better understand the ways in which teacher educators can support pre-service teachers' well-being, preparedness, and longevity in the field. Findings reveal that teachers saw their own transformative SEL-a form of SEL committed to equity and social justice (Jagers et al., 2019)-as a key factor for their success, highlighting the importance of critical and holistic preparation that focuses on the social-emotional development of teachers themselves. Implications focus on practical ways transformative SEL can be infused into teacher preparation programs including redefining success beyond student academics alone, focusing on teacher well-being in a way that does not ignore systemic oppression and school-level barriers, preparing teachers for the realities of roadblocks and ethical dilemmas they may face, and examining syllabi and coursework for the development of transformative SEL competencies.